WATER SHED MANAGEMENT AND POLICIES IN INDIA - Sharma, Tripti (International Journal of Research -GRANTHAALAYAH, 2015)
A watershed is simply the geographic area through which water flows across the land and drains into a common body of water, whether a stream, river, lake, or ocean. The watershed boundary will more or less follow the highest ridgeline around the stream channels and meet at the bottom or lowest point of the land where water flows out of the watershed, the mouth of the waterway. Much of the water comes from rainfall and storm water runoff. The quality and quantity of storm water is affected by all the alterations to the land--mining, agriculture, roadways, urban development, and the activities of people within a watershed. Watersheds are usually separated from other watersheds by naturally elevated areas. Management of the environment has been primarily focused on specific issues such as air, land, and water. Most efforts have resulted in decreasing pollutant emissions to air and water, improved landfills, remediation of waste sites and contaminated groundwater, protection of rare and endangered species, design of best management practices to control water and contaminant runoff, and much more. What is still a continuing problem for our waters are nonpoint source pollution and habitat degradation. These are the problems that are responsible for most of the water quality use impairments throughout. These are typically complex problems that are difficult to manage. Both nonpoint pollution and habitat degradation generally cross program purviews. To establish a method to tackle these remaining problems managements must come together to better understand the interactions between the environmental components and the actions that can be taken by all towards the goal of ecosystem integrity.